The Influence of Marketing Communication, Service Quality, Price and Product Quality on Repeat Purchases - Anggy Wahyu Priandini; Rita Ambarwati; Herlinda Maya Kumala Sari (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to determine the influence of marketing communications, service quality, price and product quality on repeat purchases of Mie Gacoan products in Sidoarjo This research uses quantitative research with hypothesis testing The sample used in this research was 96 respondents The analysis tool used in this research, namely the path analysis technique, was carried out using SmartPLS (Partial Least Square) software version 3.0 for Windows Primary data in this research was obtained from a questionnaire whose measurement used a Likert scale which was tested for validity and reliability The results of this research prove that marketing communication influences repeat purchases; service quality influences repeat purchases,; price influences repeat purchases,, product quality influences repeat purchases.